(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Sign Language (SL) is a method of communication using hand gestures, lip movements, and facial expressions between deaf and dumb people who were incapable of hearing and talking. This SL is very difficult to understand by the normal community. The process that converts sign images or videos into text or speech is called Sign Language Recognition (SLR). Massive research has been done for many years using different techniques. Each technique has its strengths and limitations. Sign language recognition still has challenges in recognition of double-hand gestures, complex backgrounds, fingers overlaid on palm, light effects, distance, and resolution. The main intent of this paper is to study the state-of-the-art sign language recognition techniques based on data acquisition methods, pre-processing, segmentation, feature extraction, and classification methods. Ultimately, this study may provide the reader with detailed information about sign language recognition and further research in this direction.